2010
DOI: 10.1111/j.1365-2893.2009.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection diagnosis using metabonomics

Abstract: Metabonomics based on nuclear magnetic resonance (NMR) can reveal the profile of endogenous metabolites of low molecular weight in biofluids related to disease. The profile is identified a 'metabolic fingerprint' like from the pathological process, why this metabonomics has been used as a diagnostic method. The aim of the present study was to apply metabonomics to identify patients infected with the hepatitis C virus (HCV) through an analysis of ¹H NMR spectra of urine samples associated with multivariate stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 37 publications
0
40
0
6
Order By: Relevance
“…No biological discussion of the findings was made. There has been a claim that NMR metabolomics on urine can distinguish HCV-infected from uninfected persons [90], although little data were provided. A metabolomic comparison of HCV-infected and mock-infected hepatocytes revealed small but significant increases in alanine, tyrosine and adenosine with HCV infection [91].…”
Section: The Metabolomic Window Into Other Hepatobiliary Diseasesmentioning
confidence: 99%
“…No biological discussion of the findings was made. There has been a claim that NMR metabolomics on urine can distinguish HCV-infected from uninfected persons [90], although little data were provided. A metabolomic comparison of HCV-infected and mock-infected hepatocytes revealed small but significant increases in alanine, tyrosine and adenosine with HCV infection [91].…”
Section: The Metabolomic Window Into Other Hepatobiliary Diseasesmentioning
confidence: 99%
“…The median of the patient's age who were included in this model was 61 (56-70), admission APACHE score: 22 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), admission SOFA score: 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and the length of ICU stay: 4.8 days (3.5-7.8 d). In total, 20 metabolites were significant for the differentiation among these two patient groups.…”
Section: Mortality Modelmentioning
confidence: 99%
“…It is based on the use of analytical platforms such as nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS) (13)(14)(15) (for more information about NMR and MS techniques, see the online data supplement, Supplemental Digital Content 1, http://links.lww.com/CCM/A796). It has already been demonstrated that metabolomics is an efficient technique for the discovery of molecular markers of various infectious diseases, for example, hepatitis C virus infections (16) or urinary tract infections (17). In the current study, we have used 1 H NMR spectroscopy and a quantitative metabolic profiling approach (18) to detect specific metabolic fingerprints of adult septic shock patients in the ICU.…”
mentioning
confidence: 99%
“…Metabolomics is defined as "the quantitative measurement of the metabolic response of living systems to pathophysiological stimuli or genetic modification" (13,14) and is based on analytical platforms such as proton nuclear magnetic resonance spectroscopy ( 1 H NMR) and/or mass spectrometry (13,14). It has been described that metabolomics is a very efficient tool for discovering biomarkers of various infectious diseases, such as severe childhood pneumonia (15) or hepatitis C virus infection (16). So far, most of metabolomics studies associated with sepsis have been reported for animal models (17)(18)(19), and there have been no published metabolomics studies of pediatric septic shock.…”
mentioning
confidence: 99%